Notes on seven Aglaopheniids (Cnidaria: Hydrozoa: Aglaopheniidae) from Andaman and Nicobar Islands with three new records to India - Chakraborty, Oishinee; Raghunathan, C. (Zootaxa, 2020)
Aglaopheniids were sampled from 48 survey locations in the Andaman and Nicobar Islands during September 2016 to January 2019. Seven species were encountered during the study period, of which three are first reports to India recorded from Andaman and Nicobar Islands, viz., Aglaophenia cupressina Lamouroux, 1816, Lytocarpia brevirostris (Busk, 1852) and L. delicatula (Busk, 1852). The descriptions of 4 species, viz., Gymnangium hians (Busk, 1852), Macrorhynchia philippina Kirchenpeuner, 1872, M. phoenicea (Busk, 1852) and Monoserius pennarius (Linnaeus, 1758), are provided after a taxonomic gap of 108 years from the Islands. Hydroids were observed to be growing on a variety of substrates; rocks, boulders, dead corals, polychaete tubes, ship hull and sand. Some associated fauna was catalogued as well such as the bivalve, Pterelectroma physoides (Lamarck, 1819) associated with G. hians (Busk, 1852), L. delicatula (Busk, 1852), M. phoenicea (Busk, 1852) and M. philippina Kirchenpauer, 1872. The hydroid specific nudibranch Lomanotus vermiformis Eliot, 1908 was observed on M. philippina Kirchenpauer, 1872 and an unidentified sea anemone was observed on the hydrocaulus of M. pennarius. The bathymetric distribution of the aglaopheniids were observed to be between 3–20m, with L. brevirostris and M. pennarius occurring in deeper waters, i.e., 10–20m.